Bioactivity-guided isolation of antimicrobial agent from Alternanthera Sessilis - Bakhtiar, M. Taher ([s.n.], 2011)
Alternanthera sessilis (sessile joyweed) is a herb belongs to the family of Amaranthaceae and widely used as traditional medicine in Malaysia, China, Taiwan, India and Sri Lanka. The use of this plant for antimicrobial purpose is an interesting aspect to be studied. The research was done by bioactivity-guided fractionation of the extract on their antimicrobial effects. The antimicrobial activity was performed using disc diffusion method. The antimicrobial activity of the extracts were tested against twelve strain of bacteria such as Enterococcus faecalis, Escherichia coli, Proteus mirabilis, Pseudomonas aeruginosa, Klebsiella pneumoniae, Shigella dysenteriae, Salmonella paratyphi, Propionibacterium acnes, Staphylococcus epidermidis, Staphylococcus saprophyticus, Bacillus subtilis, Staphylococcus aureus. The ethyl acetate extract of A. sessilies exhibited a moderate activity against S. aureus, S. saprophyticus, E.coli and P.aeruginosa with diameter inhibition of 15, 20, 15 and 15 mm, respectively. In addition of abovementioned sample, ten Malaysian medicinal plants were also examined. Among the sample tested, only Orthosiphon stamineous and Averrhoa belimbi possessed antimicrobial properties. O. stamineus was found to be active against S. saprophyticus and B. subtilis with MIC value of 2.5 and 0.625 mg/mL, respectively. A. belimbi had MIC value of 2.5 mg/mL against S. dysenteriae.